Microwave-Induced Self-Healing Performance of Asphalt Concrete Wearing Course (AC-WC) Mixtures Incorporating Beach Sand as Fine Aggregate - Sunarjono, Sri; Rani, Hafnidar A.; Widodo, Hanafi Satria; Fathurrahman, Adnan Nur; Azmi, Hafidzul; Syammaun, Tamalkhani; Rachman, Firmansyah; Harnaeni, Senja Rum (Engineering, Technology & Applied Science Research, 2026)
This study investigates the microwave-induced self-healing performance of AC-WC mixtures incorporating beach sand as a partial replacement for fine aggregate. Beach sand was substituted at levels of 0%, 10%, 15%, and 25% by weight of fine aggregate. Marshall tests were conducted to evaluate the mechanical and volumetric properties of the mixtures, while self-healing performance was assessed through repeated fracture and microwave heating cycles with heating durations of 40 s, 60 s, and 80 s. The results show that increasing beach sand content leads to a gradual reduction in Marshall stability and mixture stiffness, accompanied by an increase in flow values. Nevertheless, all mixtures satisfied the Marshall and volumetric requirements specified in the 2018 Bina Marga General Specifications. The self-healing evaluation indicates that the Healing Ratio (HR) improves with increasing beach sand content and longer microwave heating durations. The highest final HR of 3% was achieved at a beach sand content of 25% with heating durations of 60 s and 80 s. Among the evaluated heating durations, 60 s provided the most stable healing performance over repeated cycles, indicating an optimal balance between heat transfer and material integrity. Overall, the incorporation of beach sand as fine aggregate combined with microwave activation enhances the self-healing capability of AC-WC mixtures while maintaining acceptable mechanical performance.